Zmiany w handlu rybami i przetworami rybnymi po przystąpieniu Polski do Unii Europejskiej - Pawlak, Edyta (Changes in Trade of Fish and Fish Products after Poland's Accession to European Union, 2006)
Poland's accession to the European Union's structures resulted in a need of adopting rules of the Common Trade Policy along with the application of the EU customs tariffs. The aim of this paper is to present changes in the volume, value, structure and geographical directions of the Polish imports of fish and fish products before and after Poland's accession to the EU. Furthermore, the paper deals with the influence of applying the EU customs tariffs on the Polish imports of fish and fish products.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 206-211